Analisis Efektifitas Program Magang Untuk Sinkronisasi Link And Match Perguruan Tinggi Dengan Dunia Industri: Studi Terhadap Program Magang Pada Fakultas Ekonomi Prodi Manajemen Universitas Muhammadiyah Sumatera Utara - Muslih Muslih (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This research aimed to find industrial needs about student’s ability and skill during apprentice at company.  This research is descriptive quantitative, which is using questionair to collected data from the respondent. The result showed that, the apprentice program had be effective enough, but there were still constraints that faced by student. The constraint were soft skill, communication, interaction, adaptation, discipline dan computer skill.  The most usefull competence were computer skill and soft skill to connected to the people.